2019
DOI: 10.3949/ccjm.86a.18044
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury after hip or knee replacement: Can we lower the risk?

Abstract: Patients who undergo hip or knee replacement (total joint arthroplasty) face a risk of acute kidney injury that may be higher than previously thought and that increases steeply if they undergo surgical revision to treat prosthetic joint infection. This article assesses the incidence of and risk factors for acute kidney injury after primary total joint arthroplasty or placement of an antibiotic-loaded cement spacer to treat infection, and offers suggestions on how to reduce the risk. KEY POINTS Using current di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 82 publications
0
7
0
7
Order By: Relevance
“…Acute kidney injury is a frequent complication of total joint arthroplasty. 12 In the case presented here, the patient’s serum creatinine levels increased significantly during the course of treatment, suggesting that the decreased renal function was most likely the principal factor that led to an increased exposure to ceftazidime (Figure 2). The dosage of ceftazidime was not reduced in the context of renal impairment.…”
Section: Discussionmentioning
confidence: 74%
“…Acute kidney injury is a frequent complication of total joint arthroplasty. 12 In the case presented here, the patient’s serum creatinine levels increased significantly during the course of treatment, suggesting that the decreased renal function was most likely the principal factor that led to an increased exposure to ceftazidime (Figure 2). The dosage of ceftazidime was not reduced in the context of renal impairment.…”
Section: Discussionmentioning
confidence: 74%
“…When considering hand‐mixed high‐dose ALBC for the treatment of PJI, surgeons must balance the need to deliver a sufficient antibiotic dose that can act against infective organisms, and the risk that absorption of the local antibiotic may exceed systemic clearance, leading to systemic toxicity. The risk of organ toxicity should not be taken lightly, with the incidence of AKI ranging from 5% to 24% in cases of PJI treated with antibiotic spacers 43 . Variation in AKI occurrence is multifactorial partly explained by discordance in the literature regarding how nephrotoxic states are defined.…”
Section: Resultsmentioning
confidence: 99%
“…Variation in AKI occurrence is multifactorial partly explained by discordance in the literature regarding how nephrotoxic states are defined. AKI is associated with the use of aminoglycosides and vancomycin which are nephrotoxic antibiotics 43 . Yet, in addition to selecting an antibiotic and its dose, surgeons must also consider the brand of cement they use, how the cement and antibiotics are mixed, and whether supplementary agents should be utilized to improve the antibiotic elution as detailed in Supporting Information 1 (https://www.ors.org/wp-content/uploads/2019/12/Supplement-1.pdf).…”
Section: Resultsmentioning
confidence: 99%
“…Acute postoperative kidney injury was signi cantly correlated with increased length of hospital stay [10]. Acute kidney injury may complicate up to 10% of primary lower-extremity total joint arthroplasties and up to 25% of periprosthetic joint infections treated with a 2-stage procedure, including placement of an antibiotic-loaded cement spacer in the rst stage [10,[13][14][15][16][17][18][19][20][21][22]. None of the above studies showed the reversibility of AKI in the immediate postoperative period following hip and knee arthroplasty.…”
Section: Introductionmentioning
confidence: 99%